2013
DOI: 10.1002/trtr.1192
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Language Skills of English Learners Through Dramatization and Movement

Abstract: How can K-2 teachers foster the language development of students who have limited English backgrounds? This article explores using performing arts activities to boost the oral language skills of English learners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 14 publications
0
31
0
Order By: Relevance
“…Other prior research has shown increased engagement for students who participated in TAP (Hinga et al, 2012 ). Preliminary quantitative analyses on a smaller implementation of this program have suggested that it was effective in boosting the oral language skills of young ELs (Greenfader & Brouillette, 2013 ).…”
Section: Present Studymentioning
confidence: 99%
“…Other prior research has shown increased engagement for students who participated in TAP (Hinga et al, 2012 ). Preliminary quantitative analyses on a smaller implementation of this program have suggested that it was effective in boosting the oral language skills of young ELs (Greenfader & Brouillette, 2013 ).…”
Section: Present Studymentioning
confidence: 99%
“…The finding that the STEAM lessons were as beneficial to children who spoke English at home as to English learners was unexpected. Earlier research with K-2 English learners in San Diego (Brouillette, Grove & Hinga, 2015;Greenfader & Brouillette, 2013, 2017Greenfader, Brouillette & Farkas, 2015) led us to believe that arts integration was especially helpful for young English learners. But our findings suggest that, at least in the highpoverty urban schools where we worked, all children benefitted equally from the use of STEAM lessons to help them to envision phenomena that they were not able to directly observe.…”
Section: Results Of the Quantitative Studymentioning
confidence: 97%
“…Chand-O'Neal's (2014) research focused on a turnaround model of arts integration as a means of increasing student engagement. Greenfader and Brouillette (2013) provided compelling evidence that arts-integrated pedagogical practices improved student engagement among a population of students identified as ELLs.…”
Section: Theoretical Framementioning
confidence: 97%
“…Arts integration benefits both hard skills, measured by tests, and soft skills, or, what is referred to as non-cognitive factors, typically associated with workforce development (Kautz, Heckman, Diris, Ter Weel, & Borghans, 2014). When elementary classroom teachers integrate the arts with non-arts subjects, students' ELA achievement improves, particularly achievement associated with literate language features (Anderson, 2012;Anderson & Loughlin, 2014), speaking and listening skills (Greenfader & Brouillette, 2013), and high stakes tests (Walker, Bosworth McFadden, Tabone, and Finklestein, 2011). In tandem, integrating the arts also points to increased mathematics achievement, specifically success related to problem solving and using mathematical symbols (An, Capraro, and Tillman 2013), improved student attitudes regarding math (Werner, 2011), and higher standardized test achievement in state high-stakes math assessments (Cunnington et al, 2014;Harloff, 2011).…”
Section: Review Of Related Literature On Arts Integrationmentioning
confidence: 99%